2000
DOI: 10.1007/s002130050032
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of muscarinic, rather than nicotinic, receptors impairs attention, but does not interact with serotonin depletion

Abstract: 5-HT system is not essential for the modulation of attention, but it is important in the modulation of response control. Central muscarinic receptors are important in the modulation of attention, whereas central nicotinic receptors may be more essential in response control. The results do not support there being an interaction between the serotonergic and the cholinergic systems in the modulation of attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 45 publications
3
23
1
Order By: Relevance
“…Behavioral studies with experimental animals demonstrated that some neurotoxin lesions of the basal forebrain-cortical cholinergic system induced profound deficits of attentional processes in a five-choice serial reaction time task, and scopolamine, a muscarinic receptor antagonist, but not mecamylamine, a nicotinic receptor antagonist, impaired attentional processes. 9,[17][18][19][20] Thus these facts suggest that the cholinergic system, especially muscarinic receptors, may be essential for attention and arousal. The low dose (0.3 mg/kg) of methamphetamine significantly shortened the CRT, in agreement with the findings of a previous study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Behavioral studies with experimental animals demonstrated that some neurotoxin lesions of the basal forebrain-cortical cholinergic system induced profound deficits of attentional processes in a five-choice serial reaction time task, and scopolamine, a muscarinic receptor antagonist, but not mecamylamine, a nicotinic receptor antagonist, impaired attentional processes. 9,[17][18][19][20] Thus these facts suggest that the cholinergic system, especially muscarinic receptors, may be essential for attention and arousal. The low dose (0.3 mg/kg) of methamphetamine significantly shortened the CRT, in agreement with the findings of a previous study.…”
Section: Discussionmentioning
confidence: 97%
“…NR is generally disregarded in the visual discrimination task, although omissions are used in some tasks, because a CR is calculated not by dividing the number of CR trials by the number of total trials, but by dividing it by the total number of response trials. 7,8,17,18) In the present study, we calculated each response rate by dividing the number of each four response trials by the number of total trials, that is, 30 trials. Therefore the present method had advantages allowing the influence of various drugs and experimental treatments on the performance of a two-lever CRT task to be evaluated by measuring NR and DRO response with activity during 30 trials.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a large body of research investigating the PCA-induced impairments, most of these studies examined behavioral changes immediately after PCA administration (Solana-Figueroa et al, 2002;Archer et al, 1982;Ö gren, 1982). Ruotsalainen et al (2000) report mild impairments in response inhibition in animals 3 weeks following a neurotoxic regimen of PCA, but no impairment in a 5-choice serial reaction time task of attention. We are unaware of any studies showing lasting memory impairments in animals following 5-HT depletion by PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Mecamylamine also impaired performance in a five-choice serial reaction task in rats (Grottick and Higgins 2000), a finding in agreement with Jones et al (Jones et al 1995) who reported task-specific disruptive effects of mecamylamine in middle aged rats. However, Mirza and Stolerman (Mirza and Stolerman 1998) and Ruotsalainen and colleagues (Ruotsalainen et al 2000) only reported decrements in reaction time, not accuracy following mecamylamine administration in the five-choice serial reaction time task. In nonhuman primates, mecamylamine has been demonstrated to impair delayed matching-to-sample performance (Elrod et al 1988).…”
Section: Introductionmentioning
confidence: 95%